Tuning cyclohexane oxidation: combination of microwave irradiation and ionic liquid with the c-scorpionate [FeCl2(Tpm)] catalyst - Da Costa Ribeiro, Ana Paula (2017)
For the first time, microwave (MW) irradiation was successfully applied to peroxidative cyclohexane oxidation catalyzed by a C-scorpionate complex, [FeCl2(Tpm)] (1; Tpm = hydrotris(pyrazol-1-yl)methane), providing a highly selective and fast eco-friendly procedure to produce a KA (cyclohexanol + cyclohexanone) oil mixture (up to ca. 100% selectivity) with 28% yield in 1 h at 50 degrees C in MeCN. Water, organics, and ionic liquids (ILs, [bmim][N(CN)(2)] and [brnim][BF4]) were used as solvents, and their interactions with 1 were determined by DFT calculations. The possibility to recycle and reuse 1 (up to nine consecutive cycles) without loss of activity is also observed for the IL [bmim] [BF4]. Moreover, higher catalytic activities under additive-free conditions are obtained with the ILs in comparison to those with the other solvents. Tuning the alcohol/ketone selectivity is also possible by choosing the appropriate IL solvent.